Seribu Peta Citra Desa dan Pembangunan Pedesaan - Taryono Taryono; Agus Anggoro Sigid; Priyono Priyono (UM Purwokerto Press, 2024)
This article discusses the importance of rural development planning supported by the availability of spatial data in the form of maps. The